2019
DOI: 10.1371/journal.pgen.1007759
|View full text |Cite
|
Sign up to set email alerts
|

Balancing selection at a premature stop mutation in the myostatin gene underlies a recessive leg weakness syndrome in pigs

Abstract: Balancing selection provides a plausible explanation for the maintenance of deleterious alleles at moderate frequency in livestock, including lethal recessives exhibiting heterozygous advantage in carriers. In the current study, a leg weakness syndrome causing mortality of piglets in a commercial line showed monogenic recessive inheritance, and a region on chromosome 15 associated with the syndrome was identified by homozygosity mapping. Whole genome resequencing of cases and controls identified a mutation cau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…Chen et al [41] found that the FABP3 (HinfI) SNP was associated with IFC in both Yanan ( p < 0.001) and DLY ( p < 0.05) pigs, but did not significantly affect the BF thickness, strikingly similar to the results in our study. Although the rs344435545 SNP in the RYR1 gene is likely to cause an increase in the incidence of porcine stress syndrome, there is a strong correlation between IFC and RYR1 gene expression level [42] and as this mutation can cause a decrease of BF thickness, it has been considered as an example of balanced selection [43]. The SCD (rs80912566) SNP could affect the fatty acid composition and IFC within the Duroc population [18].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [41] found that the FABP3 (HinfI) SNP was associated with IFC in both Yanan ( p < 0.001) and DLY ( p < 0.05) pigs, but did not significantly affect the BF thickness, strikingly similar to the results in our study. Although the rs344435545 SNP in the RYR1 gene is likely to cause an increase in the incidence of porcine stress syndrome, there is a strong correlation between IFC and RYR1 gene expression level [42] and as this mutation can cause a decrease of BF thickness, it has been considered as an example of balanced selection [43]. The SCD (rs80912566) SNP could affect the fatty acid composition and IFC within the Duroc population [18].…”
Section: Discussionmentioning
confidence: 99%
“…In animal breeding, low Ne increases the risk that detrimental alleles rise in frequency by chance. Moreover, previous studies have shown that recessive lethal alleles can be driven by advantageous effects in heterozygotes (Derks et al, 2018; Matika et al, 2019). Matika et al, 2019 found a recessive stop-gained mutation in the MSTN gene associated with a major increase in muscle depth in heterozygotes.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, piglet mortality is a complex phenotype and depends on the capacity of the sow to raise its offspring, but is also a function of birth weight, management, and selection (Knol et al, 2002). However, also monogenic recessive defects contribute to piglet mortality, although only few examples have been reported in the past (Murgiano et al, 2012; Matika et al, 2019). Even in those cases where the effect of the mutation is severe, selecting efficiently against such a mutation is hampered by the low frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The recent development of sequencing and genotyping technologies for pigs have enabled the exploration of genomic evidence of selection and the detection of candidate genes associated with target traits. Studies have found that the positive selection of pigs is associated with specific genes related to lactation [ 5 ], reproduction [ 6 , 7 ], meat quality [ 8 ], and growth traits [ 9 ]. Reproductive traits, such as the number of piglets born alive (NBA) [ 10 ], lactation capacity, number of piglets weaned (NW) [ 11 ], and litter weight at weaning (LWW) [ 12 ], have all been genetically improved through artificial selection.…”
Section: Introductionmentioning
confidence: 99%